Provision of POC Banana Peel with the Addition of Moringa Leaves to the Growth and Production of Glutinous Corn (Zea mays Ceratina) - Mukarommah, Endah; Andarula Galushasti (International Integrated Agricultural Journal (IIAJ), 2025)
Optimizing the use of inorganic fertilizers through the manufacture of liquid organic fertilizers for the growth and production of glutinous corn. This study aims to analyze the effect of the application and concentration of banana peel POC on the growth and production of glutinous corn (Zea mays Caratina) plants. This research was carried out on the cultivation land of the Jember State Polytechnic, Sumbersari District, Jember Regency from August to October 2024. This study used Randomized Group Design (RAK) which consisted of 6 treatments, namely P0: No Liquid Organic Fertilizer, P1: POC banana peel with the addition of moringa leaves 40 ml/l water, P2: POC of banana peel with the addition of moringa leaves 50 ml/l of water, P3: POC of banana peel with the addition of moringa leaves of 60 ml/l of water, P4: POC of banana peel with the addition of moringa leaves of 70 ml/l of water,  P5: POC banana peel with the addition of moringa leaves 80 ml/l of water. The results of the study show that the application of Liquid Organic Fertilizer can optimize the use of inorganic fertilizers. The effect of giving POC banana peel with the addition of moringa leaves did not show a significant effect on the parameters of plant height, cob diameter, cob weight, cob weight without cob, cob length, dry pruning weight.